The impact of agricultural farmland scale management on land yield: a perspective based on the adoption of agricultural machinery in different production links - Zhang, Wenrui (Frontiers in Environmental Science, 2025)
IntroductionThe existing research on the relationship between farm size and land yield has been controversial because it fails to clarify the differences in factor substitution and technological progress across machinery technologies used in different production links.MethodsBased on micro-level farmer data from the 2020 China Rural Revitalization Survey (CRRS) database, this paper uses a stochastic Frontier model (SFM) to systematically analyze the impact of machinery technology at different production links on the relationship between the farm size and land yield of staple crops, revealing the significant role of technological progress in promoting the development of farmland scale management.ConclusionThe research results indicate that before incorporating machinery technology variables, there is an “inverse relationship” between the farm size and land yield for all three crops, meaning that the larger the farm size, the lower land yield. After incorporating machinery technology variables, the “inverse relationship” was alleviated for wheat and rice, while it was reversed for corn. After considering technical efficiency losses and adjusting the coefficients of farm size, the regression results show no significant changes. Compared to power-intensive machinery technologies, control-intensive machinery technologies have a more significant role in improving this relationship. Further analysis indicates that as farm size increases, the total factor productivity index at the farmer level for the three crops shows an upward trend, with the adoption of control-intensive machinery technologies playing an important role. Therefore, moderate-scale farming is an effective means to ensure food security, and its development process should place greater emphasis on the development and application of control-intensive machinery technologies such as spraying and fertilization.